Embryonic stem cell secreted factors decrease invasiveness of triple-negative breast cancer cells through regulome modulation. Issue 4 (3rd April 2018) - Tarasewicz, Elizabeth; Oakes, Robert S.; Aviles, Misael O.; Straehla, Joelle; Chilton, Kathryn M.; Decker, Joseph T.; Wu, Jia; Shea, Lonnie D.; Jeruss, Jacqueline S.
ABSTRACT: Stem cell microenvironments decrease the invasiveness of cancer cells, and elucidating the mechanisms associated with disease regression could further the development of targeted therapies for aggressive cancer subtypes. To this end, we applied an emerging technology, TRanscriptional Activity CEll aRray (TRACER), to investigate the reprogramming of triple-negative breast cancer (TNBC) cells in conditions that promoted a less aggressive phenotype. The repressive environment was established through exposure to mouse embryonic stem cell conditioned media (mESC CM). Assessment of carcinogenic phenotypes indicated that mESC CM exposure decreased proliferation, invasion, migration, and stemness in TNBC cells. Protein expression analysis revealed that mESC CM exposure increased expression of the epithelial protein E-cadherin and decreased the mesenchymal protein MMP9. Gene expression analysis showed that mESC CM decreased epithelial to mesenchymal transition (EMT) markers fibronectin, vimentin, and Snail. Over a period of 6 d, TRACER quantified changes in activity of 11 transcription factors (TFs) associated with oncogenic progression. The EMT profile was decreased in association with the activity of 7 TFs (Smad3, NF-κΒ, MEF2, GATA, Hif1, Sp1, and RXR). Further examination of Smad3 and GATA expression and phosphorylation revealed that mESC CM exposure decreased noncanonical Smad3 phosphorylation and Smad3-mediated gene expression, increased GATA3 expression and phosphorylation, and resulted in a synergistic decrease in migration of GATA3 overexpressing MDA-MB-231 cells. Collectively, the application of TRACER to examine TF activity associated with the transition of cancer cells to a less aggressive phenotype, as directed by mESC CM, identified novel mechanistic events linking the embryonic microenvironment to both favorable changes and cellular plasticity in TNBC cell phenotypes.